2017
DOI: 10.1177/1754073917708613
|View full text |Cite
|
Sign up to set email alerts
|

How Efficient Are Emotional Intelligence Trainings: A Meta-Analysis

Abstract: This multilevel meta-analysis examines whether emotional intelligence (EI) can be enhanced through training and identifies training effects' determinants. We identified 24 studies containing 28 samples aiming at increasing individual-level EI among healthy adults. The results revealed a significant moderate standardized mean change between pre-and post-measurement for the main effect of EI training, and a stable pre-to follow-up effect. Additionally, the type of EI model, dimensions of the four branch model, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
178
3
21

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(250 citation statements)
references
References 57 publications
12
178
3
21
Order By: Relevance
“…To understand this result we have to consider that skills of understanding and recognizing one's own emotions are the most easily modifiable with training interventions; for the development of hierarchically superior competences, 37 such as the use of emotions as facilitators of thought or the ability to regulate emotions, more time and exercise could be required. 31,38 This partial result can lay the foundation for the development of other EI skills, as noted by Joseph and Newman 37 in their cascading model: the ability to understand emotions is conceptualized as a precondition for the ability to regulate emotions.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…To understand this result we have to consider that skills of understanding and recognizing one's own emotions are the most easily modifiable with training interventions; for the development of hierarchically superior competences, 37 such as the use of emotions as facilitators of thought or the ability to regulate emotions, more time and exercise could be required. 31,38 This partial result can lay the foundation for the development of other EI skills, as noted by Joseph and Newman 37 in their cascading model: the ability to understand emotions is conceptualized as a precondition for the ability to regulate emotions.…”
Section: Discussionmentioning
confidence: 84%
“…Perhaps the development of all the emotional abilities would take more time and more complex exercise. 31 Future studies could intensify and extend the work done at school by integrating home videogame activities. Both serious and commercial games can be used at school under the teacher's guidance and promoted as homework through specific exercises.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis showed that EI trainings actually increase EI, that ability EI is less resistant to change than mixed EI or TEI, and that improvements are maintained over time (Hodzic, Scharfen, Ripoll, Holling, & Zenasni, 2018). Given that mixed EI or TEI is amenable to some change which in turn likely improves the relationship quality (Kotsou, Nelis, Gr egoire, & Mikolajczak, 2011), it seems promising to implement EI training in couple counseling (for an exemplary training schedule see Kotsou et al, 2011) and to test its effects on adaptive processes, relationship quality, and relationship stability.…”
Section: Discussionmentioning
confidence: 99%
“…According to Hodzic, Scharfen, Ripoll, Holling, and Zenasni (2018), the reasons are multifaceted, including a reluctance to publish on EI training because of commercial/intellectual property concerns and difficulties associated with capturing authentic stress responses in the field. Studies of EI and stress typically use self-report surveys, which are limited by impression management and other issues.…”
Section: Emotional Intelligencementioning
confidence: 99%